High Commitment Management and their Impact in Organizational Excellence Afield Research for opinions a sample of managers in the company general Alfurat for chemical industries \Babylon - سعيد, هديل كاظم; محمد, حيدر غازي (Journal of Economics and Administrative Sciences, 2016)
In its theoretical framework, this study dealt with the subjects of high commitment management and organizational excellence, as the study came in response to the growing developments and changes in the fields of management. It includes an analysis of correlation and effect between high commitment management, which has been attracting a lot of attention recently due to the intensifying rivalry between organizations because of certain external factors like globalization and world markets liberation, and its effect in achieving organizational excellence. The practical framework, on the other hand, dealt with the analysis of correlation and effect between the study's variables. The problem of the study  achieving excellence in performance by pushing for developing workers' skills as well as granting such workers the power to take part in the decision-making process in order to achieve organizational excellence. The study relied on a number of major and secondary hypotheses related to the existence of a moral relationship between high commitment management and organizational excellence. The study concluded that high commitment management has a positive effect on organizational excellence, and this is compatible with the statistical framework of the study's hypotheses. The current study recommends the adaptation of high commitment management in organizations that underwent the study in order to achieve the companies' vision, strategy and goals.